1990
DOI: 10.1017/s002428299000010x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological strategies of lichens

Abstract: Survival strategies of 34 species of lichens from a range of substrata, climates and growth forms were examined using the triangular ordination procedure of Grime. Triangular ordination is apparently an appropriate technique to apply to lichens, all available data falling within a triangle except for two foliicolous species which are probably partial leaf parasites. Statistically significant relationships between survival strategy and growth form, mode of asexual reproduction, substratum preference, family aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
9

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 28 publications
5
72
0
9
Order By: Relevance
“…However, I concluded that the distribution of L. pulmonaria within this stand on the Swiss Plateau was clearly limited by its low reproductive potential, which may fail to compete with a relatively high disturbance, natural or anthropogenic, of the stand. Although on the study site the main disturbance was a local wind throw in 1928, changes in forest management (Rose 1992), including shorter cutting cycles (Denison et al 1977), are probably the main factors that may lead to a rapid disappearance of L. pulmonaria and other, especially competitive (Grime 1977;Rogers 1990), lichens.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, I concluded that the distribution of L. pulmonaria within this stand on the Swiss Plateau was clearly limited by its low reproductive potential, which may fail to compete with a relatively high disturbance, natural or anthropogenic, of the stand. Although on the study site the main disturbance was a local wind throw in 1928, changes in forest management (Rose 1992), including shorter cutting cycles (Denison et al 1977), are probably the main factors that may lead to a rapid disappearance of L. pulmonaria and other, especially competitive (Grime 1977;Rogers 1990), lichens.…”
Section: Discussionmentioning
confidence: 95%
“…Lichenized ascomycetes have evolved an impressive range of symbiotic and aposymbiotic propagules (Poelt 1993(Poelt , 1994Biidel & Scheidegger 1995) that are adapted to different ecological (Rogers 1990;During 1992) and reproductive (Bowler & Rundel 1975) strategies. After dispersal to a new habitat (Bailey 1976), fixation, germination and subsequent juvenile development (van der Pijl 1982) are essential steps for successful reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Bohn et al, 2011): the absolute increase in cover per area of ground is both limited by the already existing cover, which generates the new biomass, as well as the free area that is still available for the growth of new cover. The transition of new cover from the existing cover to the free area may take place in the form of spores or via vegetative growth (Grime et al, 1990;Rogers, 1990). The efficiency of these processes is summarised in the dynamic scheme by an "expansion efficiency" (see Fig.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Jørgensen (1993) suggests that the hepatic-like morphology of this lichen and the presence of UV + substances (lichexanthone derivatives) could be related to the UV-vision of insects and represent a case of mimicry or a licheninsect interaction. However, we rather interpret these characters as a case of morphological convergence where the hyphae would determine the special shape from a specific ecophysiological adaptation to the microenvironment as has occurred in other lichenized fungi (Rogers 1990). In lichens, it is very difficult to find a case of mimicry as the one supposed by Jørgensen and most reports in the literature about mimicry in lichens are hypotheses without solid evidence (Marcano et al 1995c).…”
Section: Discussionmentioning
confidence: 96%